Sistem Informasi Buku Tamu pada Kantor PT. PLN (Persero) UPDL Tuntungan Medan Berbasis Website - Aprilia Lavigne Manik; Aninda Muliani Harahap (Pusat Riset dan Inovasi Nasional, 2025)
This study discusses the development of a web-based Guest Book Information System at PT. PLN (Persero) UPDL Tuntungan Medan as a solution to the inefficiencies of manual guest registration, which is often prone to errors and data loss. The main objective of this research is to design and implement an information system that improves operational efficiency, data recording accuracy, data security, and service quality for visitors. The research employed the Waterfall Model with stages including requirement analysis, system design, implementation, and testing. The results show that the developed system successfully replaced manual processes with faster, more accurate, and integrated digital processes. Key features include guest data recording, searching, reporting, and security management through authentication. In addition to enhancing efficiency and security, the system also supports environmental sustainability by reducing paper usage. Therefore, the web-based guest book information system can serve as an effective digital solution model for improving administrative performance and organizational services.